2020
DOI: 10.3390/ani10122451
|View full text |Cite
|
Sign up to set email alerts
|

The Native Ant Lasius niger Can Limit the Access to Resources of the Invasive Argentine Ant

Abstract: Within ant communities, the biotic resistance of native species against invasive ones is expected to be rare, because invasive species are often highly dominant competitors. The invasive Argentine ant (Linepithema humile (Mayr)) often demonstrated numerical dominance against its opponents, increased aggressiveness, and ability to quickly recruit to food. The present study aimed to assess the behavioral mechanisms involved in the interspecific competition between L. humile, facing either an invasive species (La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…L. humile's strong individual memory may allow them to reliably recruit even to distant resources, while their strong reliance on social information (von Thienen et al 2014(von Thienen et al , 2016, and ability to recruit from active trails (Flanagan et al 2013), may allow them to rapidly dominate these resources once found. Indeed, the rapid discovery of new resources coupled with massive, rapid recruitment might be an important contribution to making Argentine ants competitive against native ants (Holway 1999), but see (Cordonnier et al 2020). Route learning and navigation in ants is less effective on complex routes with alternating turns, but when trail pheromones are present, error rates decrease (Czaczkes et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…L. humile's strong individual memory may allow them to reliably recruit even to distant resources, while their strong reliance on social information (von Thienen et al 2014(von Thienen et al , 2016, and ability to recruit from active trails (Flanagan et al 2013), may allow them to rapidly dominate these resources once found. Indeed, the rapid discovery of new resources coupled with massive, rapid recruitment might be an important contribution to making Argentine ants competitive against native ants (Holway 1999), but see (Cordonnier et al 2020). Route learning and navigation in ants is less effective on complex routes with alternating turns, but when trail pheromones are present, error rates decrease (Czaczkes et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…niger is a challenging competitor that can limit the foraging success of highly invasive species such as Argentine ants (Linepithema humile ; Cordonnier, Blight, Angulo, & Courchamp, 2020). However, it is possible that, over time, T. magnum can displace L. niger from baits (Thomas and Holway 2005;Carval et al 2016).…”
Section: Effects Of T Magnum On Native Ants' Foraging Activity In Tim...mentioning
confidence: 99%
“…It has been demonstrated that the presence of L. neglectus is a weak deterrent to hinder L. humile resource exploitation, contrarily to other Lasius species (Cordonnier et al . 2020), thus the competition outcomes in the field may be also influenced by other factors, such as chemical repellents (Sorrells et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we do not know how fighting ability interacts with other behaviors, such as the ability to locate food items (Mailleux et al 2011a,b), or how lack of resources affects colony productivity and growth (Dussutour & Simpson 2008). It has been demonstrated that the presence of L. neglectus is a weak deterrent to hinder L. humile resource exploitation, contrarily to other Lasius species (Cordonnier et al 2020), thus the competition outcomes in the field may be also influenced by other factors, such as chemical repellents (Sorrells et al 2011). Moreover, since the confrontations in this study were between groups of equal size, we do not know how the final outcome varies when groups of different sizes are involved (Batchelor et al 2012;Trigos-Peral et al 2021).…”
Section: Discussionmentioning
confidence: 99%